Impact of a Modified Discharge Program on Health Outcomes After Coronary Bypass Surgery: A Randomized Trial - Hayat S. Abu Shaikha; Duaa AL Maghaireh; Mariam Kawafha; Jafar A. Alshraideh (Medicinski glasnik, 2025)
Aim: This study examines the effects of implementing a modified Re-Engineered Discharge (RED) intervention on Major Adverse Cardiovascular and Cerebrovascular Events (MACCE) and readmission rates 30 days after Coronary Artery Bypass Graft (CABG) surgery. Methods: A randomized clinical trial was conducted with 104 participants who underwent elective CABG surgery. Participants were randomly assigned to either an intervention group or a control group. The intervention group received discharge training through the modified re-engineered discharge program, while the control group followed the standard discharge protocol used at the center. Data on major adverse events and readmission rates were collected 30 days after discharge. Results: The results indicated no statistically significant differences between the intervention and control groups regarding major adverse events and readmission rates post-discharge. Both groups showed similar outcomes after the implementation of the modified re-engineered discharge program. Conclusion: This study contributes to the growing body of research on discharge interventions by providing insights into the challenges of integrating structured programs into routine care. It highlights the importance of comprehensive planning, resource allocation, and extended follow-up to enhance patient outcomes in cardiac surgery.
Keywords: Discharge; Program; Coronary Bypass; surgery; Health; Outcome